Pengaruh Jarak Tempuh Terhadap Viskositas Oli A, B dan C Pada Sepeda Motor Yamaha Mio Tahun 2011 - Erwin Susetyo Hadi; Mulyadi Mulyadi (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2017)
Lubrication can be interpreted as the provision of lubricants on a machine with the aim to prevent direct contact between the moving surfaces. Viscosity is a very important trait in lubricating oils. The viscosity of lubricating oil indicates the ability and ease of lubricating oil flowing. Distance is a number that indicates how far an object changes position through a particular path. This research method using Yamaha mio 110 cc motorcycle. Using SAE 10W-40 oil with the initial viscosity of oil A(3.17), B (5,18 ), C (15,0 ). Then tested with a distance of 30.60 and 90 km with a constant speed of 70 km / h and then taken the oil sample. The result of the test is calculated using the viscosity formula with the law of Stockes. When it was on 90 km speed, Oil C still shows the highest viscosity with a value of 2.55, while oil A remains the lowest viscosity with a value of 1.70 . This study shows that the higher the viscosity affects lubrication. The more oil layers, the lubrication can do better and the duration to changes the oil will affected too (longer).